Characteristics associated with disease prevalence, SCORTEN, length of stay, and mortality in hospitalized SJS/TEN patients: A single-center, eleven-year experience. Issue 3 (July 2022) - Duplisea, Michael J.; Ziemer, Carolyn M.; Laughon, Sarah L.; Williams, Felicia N.
Highlights: SJS/TEN patients were predominantly female, and Black suggesting a health disparity. Length of stay was significantly longer for female patients with SJS/TEN than male patients. Hypertension, diabetes, and chronic obstructive pulmonary disease were associated with increased mortality. Abstract: Stevens-Johnson syndrome (SJS), toxic-epidermal necrolysis (TEN), and SJS-TEN overlap syndrome form a continuum of rare, life-threatening disease that often warrants immediate and intensive treatment in a burn center. Our objective in this study was to determine factors associated with the prevalence, severity, and mortality in patients with Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS/TEN) admitted to our center. We performed a retrospective analysis of 192 patients admitted to our burn center from 1 January 2009 to 31 December 2019 for SJS/TEN. Severity-of-illness Score for TEN (SCORTEN), length of stay, and inpatient mortality were analyzed. Of 192 patients, 104 (54%) were Black, 117 (61%) were female, and 39 (20%) had a pre-existing psychiatric illness. Overall, 43 (22%) patients died. Female patients had significantly longer lengths of stay, with a median length of stay of 21 days versus 11 days for males ( P  =.001). Among female patients, 31/117 (26%) died compared to 12/75 (16%) of male patients ( P  =.056). Females tended to have a higher SCORTEN, but the difference was not statistically significant ( P  =.061). Hypertension, chronic obstructive pulmonary disease, and diabetes mellitus were all associated with mortality ( P  <.001). Black and female patients each represented a seemingly disproportionate percentage of our patients and females had longer lengths of stay. Future studies looking at sex- and race-based differences are needed to better understand these potential disparities.